Liver manipulation during liver surgery in humans is associated with hepatocellular damage and hepatic inflammation. (29th January 2013) - van den Broek, Maartje A. J.; Shiri‐Sverdlov, Ronit; Schreurs, Joris J. W.; Bloemen, Johanne G; Bieghs, Veerle; Rensen, Sander S; Dejong, Cornelis H C; Olde Damink, Steven W M
Abstract Background Manipulation of the liver during liver surgery results in profound hepatocellular damage. Experimental data show that mobilization‐induced hepatocellular damage is related to hepatic inflammation. To date, information on this link in humans is lacking. As it is possible to modulate inflammation, it is clinically relevant to unravel this relationship. Aim This observational study aimed to establish the association between liver mobilization and hepatic inflammation in humans. Methods Consecutive patients requiring mobilization of the right hemi‐liver during liver surgery were studied. Plasma samples and liver biopsies were collected prior to and directly after mobilization and after transection of the liver. Hepatocellular damage was assayed by liver fatty acid‐binding protein (L‐FABP) and aminotransferase levels. Hepatic inflammation was determined by (a) immunohistochemical identification of myeloperoxidase (MPO) and CD68‐ positive cells and (b) hepatic gene expression of inflammatory and cell adhesion molecules (IL‐1β, IL‐6, IL‐8, VCAM‐1 and ICAM‐1). Results A total of 25 patients were included. L‐FABP levels increased significantly during mobilization (301 ± 94 ng/ml to 1599 ± 362 ng/ml, P = 0.008), as did ALAT levels (36 ± 5 IU/L to 167 ± 21 IU/L, P < 0.001). A significant increase in MPO (P = 0.001) and CD68 (P = 0.002) positive cells was noticed in the liver after mobilization. The number of MPO‐positive cells correlated with the duration of mobilization (Pearson correlation=0.505, P = 0.033). Hepatic gene expression of pro‐inflammatory cytokines IL‐1β and IL‐6, chemo‐attractant IL‐8 and adhesion molecule ICAM‐1 increased significantly during liver manipulation. Conclusions Liver mobilization is associated with hepatocellular damage and liver inflammation, as shown by infiltration of inflammatory cells and upregulation of genes involved in acute inflammation.